MAPESA'S Role in Protecting Aceh Historical Site: (Study at Historical sites in Banda Aceh and Aceh Besar) - Anismar; Ibrahim, Mohd Yusri Bin; Muhammad, Zikri Bin; Saputra, Jumadil (International Journal of Criminology and Sociology, 2021)
The title of this research is "The Role of MAPESA in Protecting Aceh Historical Sites (Study on historical sites in Banda Aceh and Aceh Besar)". This research focuses on the strategies used by the MAPESA Community (Masyarakat Peduli Sejarah Aceh) in introducing Aceh's history to the community, as well as the obstacles faced by the MAPESA community in preserving Aceh's historical heritage. The purpose of this research is to find out what strategies the MAPESA Community uses in introducing Aceh's history to the community as well as the obstacles that mapesa communities face as long as they preserve historical relics in Aceh, especially in Banda Aceh and Aceh Besar. This research uses a qualitative approach using the Laswell Model strategy theory. In order to obtain accurate data and informant, data collection techniques used are observation, interview, documentation, and literature studies to find additional references to the problems studied. The results showed that the strategy used by the MAPESA community in introducing Aceh history is two ways, namely through direct communication (meuseuraya and expedition activities) and through media communication (books and social media). And there are two obstacles that MAPESA faces, namely in terms of delivering messages to the community and also technical obstacles ranging from secretariats, budgets, tools, and resources that are still minimal.